College Students' Attitudes and Knowledge Regarding Infertility (Research Journal, 2025)
Infertility is defined as the inability to conceive after 12 months or more of regular unprotected sexual intercourse. It is considered a serious reproductive health problem that is increasing in recent days. However, it is not given much attention. This study aims to find out and compare the knowledge and attitudes of college students by gender towards infertility using descriptive and inferential statistical methods.A cross-sectional survey was conducted among 165 college students studying at the Bachelor in Education at Mahendra Ratna Campus, Kathmandu. Data were collected using a structured questionnaire. Chi-square tests, and other inferential statistics were used to explore the relationships and differences between the variables.The majority of respondents were female (73.9%) and unmarried (87.3%). All respondents had heard of infertility, but misconceptions still persisted, with 38.5% of women and 20.9% of men believing that infertility is only a female problem. The majority (85.5%) believed that infertility can be treated. There is some disparity in misconceptions and attitudes according to gender. Religious and cultural influences were evident, with 33.3% non-Hindus and 20.6% Hindus having a modest association between religion and cultural or religious influences on infertility treatment (χ2 = 11.886, p = 0.018, phi = 0.268), but no statistically significant association between gender and misconceptions toward infertility (χ² = 7.418 and p-value = 0.060). Despite a general understanding of infertility among college students, misconceptions and gender disparities persist. Further education and public awareness about infertility, including its inclusion in school and university curriculum and public awareness campaigns that emphasize social support are needed to increase education and public awareness about infertility.